Hermeneutik: Studien über den Umgang der Jurisprudenz mit Normtexten im Vergleich zur biblischen Theologie und zur Literaturwissenschaft - Isensee, Josef (Schriftenreihe des Käte-Hamburger-Kollegs "Recht als Kultur", 2023)
Hermeneutics is the art of understanding foreign meaning and communicating it to others in words. The present studies take their point of departure from juridical hermeneutics and compare them with biblical theology and literary studies. They all depend on understanding given texts and interpreting them. But only laws and biblical messages, authoritative texts that is, can be applied and have a planned effect on the life world. Possibilities of this kind are foreign to the "beautiful" texts of poetry. They follow their own aesthetic legality. The identical text can keep open different possibilities of interpretation. These, however, are not unlimited. Hermeneutics is oriented towards truth. But this is the truth about the given text, which is independent of whether the text itself is true or not.